GE_GERICHTE C/22976/2011 vom 13. August 2013 - GE Cour de justice (2013)
PROHIBITION DE CONCURRENCE; ERREUR ESSENTIELLE; DOL(VICE DU CONSENTEMENT) | CO.23; CO.28.1; CO.31.1; CO.31.2; CO.25; CO.26; CO.340.1; CO.340a.1